Trick or treat Scooby-Doo! [videorecording (DVD)] (SDS : Warner, 2022)
It's Halloween and a mysterious new enemy wants revenge against Mystery, Inc. Now they'll have to team up with their arch-nemesis the evil mastermind behind every costume in Scooby-Doo history to solve this macabre mystery. With this unpredictable new ally, Scooby and friends will learn some spooky new tricks and even don the outfits of their most famous foes to save the day on this special Halloween night.